Peter Singer e la bioetica - Pascual, L.C., Fernando (Alpha Omega, 2022)
Summary: This article aims to situate the bioethical proposals of Peter Singer within his fundamental assumptions about life, the human being, and ethics. To this end, we shall adopt the following scheme: First, there will be a brief presentation of Peter Singer’s life, his main academic activities, and his publications. Then, we shall make a synthesis of the presuppositions and principles from which the author’s bioethical proposals arise, as well as providing some general applications (the so-called “new commandments”). Next, we shall see the concrete applications of these principles in two great areas of human existence: its initial phase and its terminal phase. Finally, we shall offer some concluding remarks and critical observations on Singer’s bioethics. Key Words: Peter singer, bioethics, utilitarianism, life, abortion, euthanasia. Parole chiave: Peter Singer, Bioetica, utilitarismo, vita, aborto, eutanasia.